The Importance of IT-Based Public Accounting Transformation in Supporting the Digitalization of Good Governance - Ningsih, Fidrya (PT FORMOSA CENDEKIA GLOBAL, 2023)
The writing of this article aims to analyze the importance of IT-based public accounting transformation in order to support the digitalization of good governance. The existence of a negative stigma that states that one day the role of accountants will be replaced by technological innovation products demands the role of public accounting to answer these challenges. To analyze this phenomenon, the author reviewed 15 journals from previous research and official data and government publications between 2019 and 2023. The author chooses literature review as a methodology in writing this article through a descriptive qualitative approach. The results of the review of the 15 journals show that IT-based public accounting transformation is needed in the implementation of digitalization of good governance. The adaptability of public accounting to the changes in this very dynamic era is considered capable of maintaining its existence in the midst of the digitalization storm. In relation to good governance, the application of IT-based public accounting can help accelerate the optimization of good governance if implemented consistently and sustainably. Digital track records that are difficult to eliminate can serve as a constant database for various public purposes.